X2=-13x-4

Simple and best practice solution for X2=-13x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X2=-13x-4 equation:



X2=-13X-4
We move all terms to the left:
X2-(-13X-4)=0
We add all the numbers together, and all the variables
X^2-(-13X-4)=0
We get rid of parentheses
X^2+13X+4=0
a = 1; b = 13; c = +4;
Δ = b2-4ac
Δ = 132-4·1·4
Δ = 153
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{153}=\sqrt{9*17}=\sqrt{9}*\sqrt{17}=3\sqrt{17}$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(13)-3\sqrt{17}}{2*1}=\frac{-13-3\sqrt{17}}{2} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(13)+3\sqrt{17}}{2*1}=\frac{-13+3\sqrt{17}}{2} $

See similar equations:

| -8x-2=-4x-1 | | 10(x-9)-9(5-6x=2(4x-1)+5+10x | | -10=1/3y | | 4v-v-2v=12 | | g+13=22 | | 5x+1=6x+3 | | -8b+-16=0 | | 145k=20.88 | | -20p+10p=-20 | | j+11=16 | | 28-4x=6(2x-2)+25 | | 3+4h=15 | | 8x-17=109-x | | 15a+3a-7a-2a=9 | | 0=1.6+b | | 1/5(170×b)=450 | | 10-2w=-10+3w | | {2/3x=10} | | 7.5-x=9/(-2) | | 25+3x=58 | | -9s-7=-8s | | 4(s+11)=12 | | 137=5(1-8n)-4n | | 1.5c+13=3c+48 | | 3=4h=15 | | -30=-5(r-1) | | -2w-9=-5w | | (3/2)x+2=(1/5)x+9 | | 3w–4=w+80 | | 86=-10(r-12)+16 | | 3(k+8)=21. | | 5u+-14u=-9 |

Equations solver categories